Systematic preoperative approach for bariatric surgery, perioperative results, and economic impact - Freire-Moreira, Iolanda; Sanchez-Conde, Maria Pilar; Sousa, Gilles Barreira-de; Garrido-Gallego, Maria Isabel; Rodríguez-López, José María; Juárez-Vela, Raúl; Bragado, Juan Alonso; Carretero-Hernández, Marta; Vargas-Chiarella, Carlos Ricardo; Calderón-Moreno, Jesús; Lorenzo-Gómez, María Fernanda; Vaquero-Roncero, Luis Mario (Frontiers in Public Health, 2024)
Introduction Obesity is a complex systemic condition, involving numerous anatomical and metabolic changes. Therefore, a comprehensive preoperative assessment is essential for each patient contemplating bariatric surgery. Objetive This study presents the findings of a proposed protocol designed to streamline the pre-anesthesia consultation process. Our aim was to compare the efficiency and costs of consultations guided by the protocol with those conducted without a specific strategy. The secondary outcomes assessed included postoperative (PO) length of hospital stay and surgical duration. Matherial and methods We conducted a retrospective cross-sectional analysis involving 206 clinical cases. Statistical analyses, including the chi-squared test, Student’s t-test, and Mann–Whitney U test, were utilized based on the type of variables. Results The results showed a significant reduction in the costs, pre-anesthesia consultation duration, time spent in the recovery unit, and the need for referrals. However, no statistically significant differences were observed in the delay before surgery and length of hospital stays, measured in days. Conclusion This algorithm offers a promising approach for optimizing perioperative management in bariatric surgery, demonstrating its effectiveness in cutting costs and reducing the need for referrals.